Use of Youtube as Educational Tool among Medical Students of College of Medicine at Qassim University - Alghaith, Bader Khalid; Alnughaymishi, Abdullah Saleh; AlHarbi, Dr. Muslet (International Journal of Innovative Research in Medical Science, 2020)
Purpose: This study aimed to evaluate how many medical students depends on YouTube medical videos as resources of their medical knowledge. Methods: This was a cross-sectional study with a convenience sample and validated questionnaires were distributed to medical students anonymously from the students on the medical college of Qassim University in Saudi Arabia. The study includes all male medical students and excludes the females medical students and staff members. The total number of medical students is 191 students. Results: Up to 95.3% (n= 182) of the total sample use YouTube in their education. The majority of them believe that the medical videos more understandable compared to the written lectures. Also, many students usually sharing medical videos with their colleagues. In addition, around 70% of students think that YouTube medical videos help in relating basic and clinical sciences together. Conclusion: Today social media have very important role in learning and YouTube one of the most important and effective websites in learning especially in medical field. But still the students need a specific website for medical videos under the organization of specialized tutors. In addition, medical colleges need to encourage social media usage in education.